Detection of Cytochrome P450 mRNA in Tissue Sections and Cell Lines Using Enzyme-Labeled Fluorescence In Situ Hybridization - VILLAROMAN, CATHERINE (1997)
Cytochrome P450s (P450s) constitute a superfamily of enzymes that metabolize a broad array of xenobiotics. The ability to measure basal and induced levels of P450 mRNA in specific cells and tissues should provide valuable insight regarding the functional role and heterogeneous expression of these enzymes in chemically related diseases. Methodologies for detecting cell-specific mRNA expression patterns typically rely on radiolabeled probes and photographic emulsions, often coupled with long exposure times. These studies were conducted to evaluate an enzyme-labeled fluorescence (ELF) in situ hybridization technique to detect specific P450 mRNA. Deparaffinized, formalin-fixed tissue sections and cells from culture were incubated for 12 hours with 5′-biotinylated 20-base DNA oligomer probes (20-mer). Specific hybridization was detected using a streptavidin alkaline-phosphatase conjugate followed by incubation with the ELF substrate, yielding a bright, yellow-green fluorescent signal. In this study, utility of the technique was demonstrated using cultured rat hepatorna cells, and tissue sections from rat liver and human oral epithelium. Ribonuclease A pretreatment of the sample, omission of the probe, competition with a nonbiotinylated oligomer, and the use of only partially homologous probes served as negative controls to demonstrate the specificity of the hybridization signal. Our results clearly demonstrated the ability of ELF in situ hybridization to discriminately detect cell-specific P450 mRNA in tissue sections and cultured cells. This technique eliminates the use of radioactivity and enables in situ detection of mRNAs with relative ease, efficiency, specificity, and high sensitivity.